Radiation induces an inflammatory response that results in STAT3-dependent changes in cellular plasticity and radioresistance of breast cancer stem-like cells - Arnold, Kimberly M. (Int J Radiat Biol, 2020)
PURPOSE: Pro-inflammatory cytokines within the tumor microenvironment, such as IL-6, contribute to the maintenance of stem cells and promote their survival following treatment. The IL-6/STAT3 pathway is a key regulator of genes involved in cancer progression. Activation of STAT3 promotes expansion of cancer stem cells in triple negative breast cancer. Radiation has also been shown to expand cancer stem cell populations and can induce stemness in non-stem cells. However, the role of IL-6/STAT3 in radiation induced changes in cellular plasticity is unclear. MATERIALS AND METHODS: Expression and secretion of IL-6 from triple negative breast cancer cell lines SUM159PT and MDA-MB-231 were determined after radiation treatment by real-time PCR and ELISA. Activation of STAT3 after radiation was determined by western blotting. Changes in cellular plasticity induced by radiation were determined by examining ALDEFLUOR activity, gene expression analysis of aldehyde dehydrogenase isoforms and mammosphere forming assays with and without the addition of STAT3 inhibitors. To determine the effect of radiation on non-stem cell populations, experiments were also carried out in ALDEFLUOR sorted cells. RESULTS: Radiation induced an inflammatory response in both cell lines that resulted in activation of STAT3. Additionally, radiation induced a stem-like state as evidenced by an increased activity and expression of the ALDH isoforms ALDH1A1 and ALDH1A3, and increased self-renewal capabilities. Radiation increased ALDH activity and self-renewal in non-stem cell (ALDH−) populations, suggesting radiation induced cellular reprogramming. However, inhibition of STAT3 blocked the radiation-induced stem-like state in both ALDEFLUOR positive and negative populations, and enhanced radiosensitivity. CONCLUSIONS: Radiation-induced changes in cellular plasticity are STAT3 dependent and may be a potential target to reduce radioresistance in TNBC and improve treatment outcome.